Prevalence of prehypertension and associated factors in women - José do Carmo Rocha (Investigación y Educación en Enfermería, 2014)
Objective. To estimate the prevalence of factors associated with prehypertension among 20 to 59 years old women cared for by primary healthcare units that adopted the Family Health Strategy. Method. Cross-sectional study conducted in a city in the interior of Minas Gerais, Brazil. The study's population was composed of 1,773 women with blood pressure below 140/90 mm ​​Hg. The dependent variable was prehypertension (≥120/80 mmHg to <140/90 mmHg). Results. The prevalence of prehypertension was 20.6%. The multivariate analysis showed that overweight or obese women of African descent, 40 years old or older with a family history of hypertension, had an increased risk of presenting prehypertension. Conclusion. Although the prevalence found in this study is lower than that reported by other studies, nurses need to implement efforts to prevent and detect prehypertension, especially among high-risk groups.